Kazakh Ziziphora Species as Sources of Bioactive Substances - Šmejkal, Karel; Malaník, Milan; Zhaparkulova, Karlygash; Sakipova, Zuriyadda; Ibragimova, Liliya; Ibadullaeva, Galya; Žemlička, Milan (Molecules, 2016)
Ziziphora species represent the prototypical example of the Lamiaceae family. The phytochemicals present in Ziziphora include monoterpenic essential oils, triterpenes and phenolic substances belonging to the flavonoids. In Kazakh traditional medicine, Ziziphora species possess several medicinal uses. In particular, Z. bungeana Lam. and Z. clinopodioides Lam. are used for the treatment of illnesses related to the cardiovascular system or to combat different infections. Unfortunately, the majority of the information about the complex Ziziphora species is only available in Russian and Chinese language, therefore, we decided gather all available information on Kazakhstan Ziziphora, namely its content compounds, medicinal uses and published patents, to draw the attention of scientists to this very interesting plant with high medicinal potential.
Keywords: Rhizophoraceae; Flavonoids; flavonoidy; Animals; biologické přípravky; Oils, Volatile; fytonutrienty; lidé; Phytochemicals; zvířata; Biological Products; oleje prchavé; Humans